Zweite "Tagung der Fachdidaktik" 2015 Sprachsensibler Sach-Fach-Unterricht - Sprachen im Sprachunterricht - Hinger, Barbara (Innsbrucker Beiträge zur Fachdidaktik, 2016)
This volume includes contributions that were presented in various forms at the "Second Conference of Subject-Specific Education" at the University of Innsbruck in April 2015. The motto of the conference was "Language-sensitive instruction in science and history as well as religious teaching in school contexts - languages ​​in language teaching" and took account of the overriding role of language in school-based instruction. The conference proceedings also show the orientation of the Department for Subject-specific Education at the School of Education, since it combines linguistic, scientific and religious subjects as well as mathematics under one institutional roof. - Der vorliegende Band umfasst Beiträge, die im Rahmen der "Zweiten Tagung der Fachdidaktik" an der Universität Innsbruck im April 2015 in unterschiedlichen Formen präsentiert wurden. Die Tagung stand unter dem Motto "Sprachsensibler Sach-Fachunterricht - Sprachen im Sprachunterricht" und trug der übergeordneten Rolle von Sprache im schulischen Unterricht Rechnung. Der Tagungsband zeigt auch die Ausrichtung des Instituts für Fachdidaktik an der School of Education, da dieses sprachliche, naturwissenschaftliche und religiöse Fächer ebenso wie Mathematik unter einem institutionellen Dach vereint.